Penurunan Intensitas Nyeri Menstruasi (Dysmenorrhae) dengan Kompres Hangat : Decreased Intesity of Menstrual Pain (Dysmenorrhae) With Warm Compresses - Sumiaty Sumiaty; Adel Vita Masya Dupa; Lili Suryani; Kadar Ramadhan (Jurnal Bidan Cerdas, 2021)
Introduction: Dysmenorrhea is a pain that occurs during menstruation, caused by the contraction of the uterine muscles during menstrual bleeding which can last between 32-48 hours. This study aims to determine the decrease in pain intensity before and after giving warm compresses. Method: This study used a pre-experimental study design with one group pre-test and post-test design with sample of 38 respondents. The independent variable in this study was warm compress on adolescent girls who have menstrual pain (dysmenorrhea), The dependent variable in this study was the reduction of menstrual pain (dysmenorrhea). Results: This study found giving warm water compresses can reduce 15.8% of severe pain, 60.4% of moderate pain, and almost half of the respondents after this therapy have no more pain. Wilcoxon signed-rank test results obtained p-value <0.001. Conclusion; giving warm compresses can reduce the level of menstrual pain (dysmenorrhea) among adolescent girls.